Revitalisasi Nilai Toleransi Islam dalam Sejarah Penyebaran Islam di Indonesia Studi Kasus Pendekatan Wali Songo - Deko Rio Putra; Ririn Indriyani (Yayasan Darusssalam Bengkulu, 2025)
This article discusses the revitalization of the value of Islamic tolerance in the history of the spread of Islam in Indonesia, with a focus on the Wali Songo approach. Wali Songo, as an important figure in the Islamization process in Java, applies innovative and adaptive da'wah methods, which integrate local culture with Islamic teachings. This process not only strengthens society's acceptance of Islam, but also emphasizes the importance of tolerance in social interactions amidst cultural and religious diversity. Through an in-depth literature review, this research reveals that the values ​​of tolerance taught by Wali Songo have high relevance in the current social and cultural context of Indonesia, especially in facing potential conflicts between ethnicities and religions. The results of the analysis show that revitalizing these values ​​can be a solution to creating a more harmonious and peaceful life in society. This article emphasizes that understanding and reapplying Wali Songo's teachings is important for building an inclusive Indonesian Islamic identity, as well as supporting social harmony in an increasingly complex era of globalization.